The participation of children and young people in the recruitment of residential child care staff in Scotland - Helen Kay; Irene Stevens (Scottish Journal of Residential Child Care)
In 2004, the Scottish Executive commissioned research from the Scottish Institute of Residential Child Care (SIRCC) to identify current recruitment practices in residential child care. Part of this research examined to what extent children and young people had participated in the process used. This article focuses on the findings of the research in relation to involving children and young people in recruitment and selection.